Biomass, Litter Production and Selected Nutrients in Bruguiera Parviflora (Roxb.) Wight & Arn. Dominated Mangrove Forest Ecosystem at Kuala Selangor, Malaysia - Hossain, Mahmood (2004)
This study was carried out to investigate the standing biomass, litter dynamics and selected nutrients in soil, water and plant components in a Bruguiera parviflora dominated naturally growing unmanaged mangrove forest ecosystem in Kuala Selangor Nature Park, Malaysia. This study was initiated during September 2001 and ended on August 2003. The total above and below-ground biomass of B. parviflora seedlings, saplings and trees were 144.47 t/ha and 19.93 t/ha, respectively, and the net primary productivity of this forest was 27.44 t/ha/yr. The annual amount of small litter production and small litter standing crop were 1035 g/m2 and 337.72 g/m2, respectively. Bruguiera parviflora leaf litter showed higher microbial degradation (60% of initial dry mass) in wet month (November 02) than the dry month (20.17% of initial dry mass, July 02), but leaf litter loss due to feeding plus mechanical breakdown did not vary in dry and wet months. Soil parameters (pH, redox potential, air-dry moisture, organic matter, conductivity, salinity and cation exchange capacity) and nutrients (N, P, K, Ca, Mg, S, C, Cu, Fe and Zn) were measured in intermediate (March), dry (July) and wet (November) seasons and found relatively higher organic matter (12.03-12.56%) and cation exchange capacity (37.31-38.23 m.e/100 g) in the intermediate seasons (March 02 and 03). Higher conductivity (11.25-11.81 mS/cm) and salinity (57.64-59.03 m.e/100 g) were observed during the dry seasons (July 02 and 03). Comparatively higher content of N (3.49-3.50 mg/g), P (0.33-0.34 mg/g), K (6.86-7.06 mg/g), C (63.29-67.63 mg/g) and Fe (11929.44-12866.67 g/g) in soil were observed during the intermediate seasons (March 02 and 03). Higher conductivity (55.83-71.00 mS/cm) was observed in infiltration water followed by river water (18.17-22.17 mS/cm) and relatively higher conductivity of rainwater, canopy drip, river and infiltration water was found during the dry seasons (July 02 and 03). Nutrients (NH4, NO3, PO4, K, Ca, Mg and SO4) in rainwater, canopy drip, stem flow, river and infiltration water fluctuate with the seasons and comparatively higher K, Ca, Mg, SO4, Cu, Fe and Zn were observed in infiltration water followed by river water. Nutrients (N, P, K, Ca, Mg, S, C, Cu, Fe and Zn) in different components of B. parviflora seedlings, saplings and trees were measured in intermediate (March), dry (July) and wet (November) seasons and reported comparatively higher N, P, K, Ca, Mg and Fe in plant components during the intermediate seasons (March 02 and 03) and relatively higher sulphur was found during the dry seasons (July 02 and 03). Nutrients content in different components of seedlings, saplings and trees of B. parviflora showed positive correlations with the soil nutrients level. The annual uptake range of N, P, K, Ca, Mg, S, Cu, Fe and Zn was 109.34-129.67 kg/ha, 16.70-25.65 kg/ha, 39.69-66.71 kg/ha, 153.84-240.41 kg/ha, 48.30-68.27 kg/ha, 100.93-177.05 kg/ha, 120.61-287.14 g/ha, 7981.31-14697.29 g/ha and 204.49-581.41 g/ha, respectively.